Donor brain death leads to differential immune activation in solid organs but does not accelerate ischaemia–reperfusion injury. Issue 1 (28th March 2016) - Ritschl, Paul Viktor; Ashraf, Muhammad Imtiaz; Oberhuber, Rupert; Mellitzer, Vanessa; Fabritius, Cornelia; Resch, Thomas; Ebner, Susanne; Sauter, Martina; Klingel, Karin; Pratschke, Johann; Kotsch, Katja
Abstract: A comparative analysis of inflammation between solid organs following donor brain death (BD) is still lacking and the detailed influence of BD accelerating ischaemia–reperfusion injury (IRI) post‐transplantation remains to be addressed. Applying a murine model of BD, we demonstrated that 4 h after BD organs were characterized by distinct inflammatory expression patterns. For instance, lipocalin 2 (LCN2), a marker of acute kidney injury, was selectively induced in BD livers but not in kidneys. BD further resulted in significantly reduced frequencies of CD3 + CD4 +, CD3 + CD8 + T cells and NKp46 + NK cells in the liver, whereas BD kidneys and hearts were characterized by significantly lower frequencies of conventional dendritic cells (cDCs). Syngeneic models of kidney (KTx) and heart transplantation (HTx) illustrated stronger gene expression in engrafted BD hearts only, but 20 h post‐transplantation both organs displayed comparable intragraft lymphocyte frequencies, except for NK cells and graft function. Moreover, the complement factor C3d deposit detected in small vessels and capillaries in cardiac syngrafts did not significantly differ between BD and sham‐transplanted groups. Finally, no further influence of donor BD on graft survival was detected in an allogeneic heart transplantation setting (C57BL/6 grafts into BALB/c recipients). We show for the first time that BD organs are characterized by a varying inflammatory profile; however, BD does not accelerate IRI in syngeneic KTx and HTx. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.